2021
DOI: 10.1111/1471-0528.16691
|View full text |Cite
|
Sign up to set email alerts
|

Risk of stillbirth in singleton gestations following in vitro methods of conception: a systematic review and meta‐analysis

Abstract: Background In vitro methods of conception are associated with adverse perinatal outcomes. It is unclear if the risk of stillbirth is increased also. Objective This systematic review and meta‐analysis aimed to estimate the risk of stillbirth in singleton gestations following in vitro methods of conception compared to non‐in vitro conceptions. Search strategy A comprehensive search in PubMed, Embase, CINAHL, and Cochrane Library was undertaken from database inception to February 2021, with backward citation trac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 60 publications
(114 reference statements)
1
5
0
Order By: Relevance
“…( 15 ) A meta-analysis comparing 68,274 ART-conceived and 3,570,990 conceived without medical assistance, mainly from cohort studies, also found higher odds of stillbirth after ART (OR 1.41, 95%CI 1.20-1.65). ( 14 ) Previous observations from the Nordic countries, overlapping our study population with births from 1988 to 2007, indicated similar risk of stillbirth for both frozen-ET (n=6,647) and fresh-ET (n= 42,242) compared to conceptions without medical assistance (n=288,542). ( 23 )…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…( 15 ) A meta-analysis comparing 68,274 ART-conceived and 3,570,990 conceived without medical assistance, mainly from cohort studies, also found higher odds of stillbirth after ART (OR 1.41, 95%CI 1.20-1.65). ( 14 ) Previous observations from the Nordic countries, overlapping our study population with births from 1988 to 2007, indicated similar risk of stillbirth for both frozen-ET (n=6,647) and fresh-ET (n= 42,242) compared to conceptions without medical assistance (n=288,542). ( 23 )…”
Section: Discussionsupporting
confidence: 51%
“…The lack of association between conception method and risk of stillbirth in our study is in contrast to the results from a population-based study from the Netherlands, where a nearly doubled risk of stillbirth was found for any ART (n ¼ 19,896) compared with pregnancies conceived without medical assistance (n ¼ 999,050; OR, 1.94; 95% CI 1.54-2.44) (15). A metaanalysis comparing 68,274 ART-conceived and 3,570,990 conceived without medical assistance, mainly from cohort studies, also found higher odds of stillbirth after ART (OR, 1.41; 95% CI, 1.20-1.65) (14). Previous observations from the Nordic countries, overlapping our study population with births from 1988 to 2007, indicated similar risk of stillbirth for both frozen-ET (n ¼ 6,647) and fresh-ET (n ¼ 42,242) compared with conceptions without medical assistance (n ¼ 288,542) (23).…”
Section: Comparisons To Other Studiesmentioning
confidence: 98%
See 1 more Smart Citation
“…Birth defects are closely related to the perinatal period and infant mortality ( 30 ). However, there is still no consensus on whether ART increases the incidence of neonatal birth defects.…”
Section: Discussionmentioning
confidence: 99%
“…Pregnancies conceived by ART have increased risks of complications, including hypertensive disorders of pregnancy, preterm birth, and low birth weight, with some variation by ART method. [2][3][4][5][6][7][8] A high proportion of early cohorts of people conceived by ART were part of a multiple birth, which explains some of the obstetric and perinatal outcomes, but not all. [2][3][4] Whether these risks are increased by causes of subfertility or by the ART treatments is still an ongoing debate.…”
Section: Introductionmentioning
confidence: 99%